Chelating capacity and the adverse effects of two treatments (N-acetylcysteine and D-penicillamine) in patients with mercury poisoning in Segovia, a municipality at the northeastern part of Antioquia, Colombia - Arroyave, Claudia Lucía; Molina Castaño, Carlos Federico; Suárez, Ana María; Maldonado, Natalia; Cuesta González, Fanny (Iatreia, 2008)
OBJECTIVE: to compare the chelating capacity and the adverse effects of treatments with either Nacetylcysteine or D-penicillamine in patients with mercury poisoning in Segovia, a municipality at the northeastern part of Antioquia, Colombia. METHODS: 50 patients with toxic levels of mercury were enrolled in a 10 days open label, randomized comparison of either D-penicillamine (750 mg/day) or Nacetilcysteine (1.8 g/day). Patients were followed on a daily basis to assess the elimination of mercury in urine and the frequency of adverse effects of each treatment. RESULTS: 32 patients completed 10 days of drug treatment. Averages of mercury elimination in 24 hours urine, before and after treatment with D-penicillamine and N-acetylcysteine, were not different (211.96 mcg ± 190 and 262.15 mcg ± 305 and 232.85 mcg ± 248 and 218.65 mcg ± 240, respectively, P > 0.05 for all comparisons). Evaluation of the frequency of adverse effects showed a significant difference between the two groups: D-penicillamine (50%) and N-acetylcysteine (11%) p = 0.0079. CONCLUSION: this study did not reveal any significant differences between the chelating capacity of Dpenicillamine and N-acetylcysteine in patients with mercury poisoning, from a mining population at the northeastern part of Antioquia, Colombia. However, there were significantly less adverse effects with the Nacetylcysteine treatment.